(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Saxagliptin is used in the treatment of type 2 diabetes to improve blood sugar control in combination with other drugs or as monotherapy. Sulfonate esters are formed during the synthesis of drug substances involving sulphuric acid which reacts with the alcohols thus yields alkyl and aryl esters. Sulfonate esters have the capability to undergo reaction with DNA and initiates mutagenic changes, which leads to cancerous cell generation. Therefore, the limiting of sulfonate esters in drug substances is important to the pharmaceutical products. Therefore, it is necessary to have a highly sensitive and cost effective method to monitor the sulfonate esters in the Saxagliptin drug substances. Six sulfonate esters viz., methyl, ethyl and isopropyl tosylates, as well as methyl, ethyl, and isopropyl besylates were separated and quantified using the simple direct HPLC method with highest sensitivity of 0.033 ppm as limit of detection. The method was optimized with 0.10% orthophosphoric acid in Milli-Q water as mobile phase A and 100% acetonitrile as mobile phase B in gradient elution condition in Inertsil ODS 3V (250 mm x 4.6 mm x 5 µm) column at 40 °C oven temperature with a flow rate of 1.0 mL/min. The developed method is highly sensitive, accurate, linear, and precise over the range of 0.1 to 1.5ppm. The finalized procedure was confirmed by thorough validation with the International Council for Harmonisation guidelines, where all the parameters are in good agreement with the acceptance criteria.